Improving the Quality of Education in Islamic Education Institutions - Jeri Saputra; Elvi Rahmi (Ahlussunnah: Journal of Islamic Education, 2024)
The principal is one of the key components in improving the quality of education in Islamic educational institutions. They have a strategic role in managing and developing schools, and ensuring that the educational process runs effectively and efficiently. However, there are still many questions about how the role of the principal in improving the quality of education in Islamic educational institutions. This study aims to analyze the interpersonal, communication and cooperation competencies of the principal in improving the quality of education in the school environment. This study uses a qualitative descriptive method, data sources are taken from eight informants through in-depth individual interviews. The author also conducted direct observations at the research location and analyzed several related documents to support these findings. The research findings found that related to the interpersonal competence of the principal, he carried out eight forms of performance such as collaborating with educators, conducting workshops, and holding discussions. Related to communication competence, the principal took a personal communication approach such as receiving complaints and suggestions from school residents. Furthermore, related to cooperation competence, the principal formed a solid work team, solved problems together and built partnerships with parents of students.